Molecular Mechanism of Bai-Bo Formula for Treatment of Vitiligo Based on Network Pharmacology and Molecular Docking: Bai-Bo Formula Treats Vitiligo - Zhang, Kaibo; Zhang, Bin; Song, Yeqiang (Cellular and Molecular Biology, 2023)
Using network pharmacology and molecular docking, this study aims to evaluate the pharmacological mechanism of Bai-Bo Formula in the prevention and treatment of vitiligo. The chemical composition collection and anticipated targets for Bai-Bo Formula for vitiligo were compiled using TCMSP and BATMAN-TCM databases. GeneCards, OMIM, and DisGeNET databases were used to extract targets associated with vitiligo. The acquired drug-component targets were intersected with the illness targets to identify common genes, and a drug-component-target network was created using Cytoscape 3.7.2. Protein-protein interactions of Bai-Bo Formula were examined using String, and function enrichment analyses were performed on the primary targets using gene ontology and the Kyoto encyclopaedia of genes and genomes. Finally, molecular docking technologies were used to validate the combination of primary components and key targets. A study evaluated 167 active ingredients and 1425 prediction targets in 12 traditional Chinese remedies known as Bai-Bo Formula for treating vitiligo. 169 target genes were found to interact with the medicine. The protein-protein interaction network analysis identified 91 important proteins, with the top 5 targets being IL6, TNF, AKT1, IL1, and STAT. Bai-Bo Formula regulates immune inflammation, apoptosis, and autophagy via various pathways, including AGE-RAGE, PI3K-Akt, and TNF signaling. Molecular docking indicated that the primary components could attach effectively to the target protein. Based on network pharmacology and molecular docking, the mechanism of Bai-Bo Formula in the treatment of vitiligo via multicomponent, multitarget, and multichannel was investigated in depth.